Data for SSF analysis of wolf - Courbin, Nicolas; Fortin, Daniel; Dussault, Christian; Courtois, R. (Dryad Digital Repository, 2014)
Data used to model the relative probability of making steps for wolf in winter as a function of step length and features of the networks of its prey (Table 7). Covariates are provided at observed steps and at random steps.